Isolation and identification fungi contaminated onion bulbs, detection Aspergillus spp. toxins, and inhibiting its growth by Moringa oleifera extract - Sadeq Mohammed Ali; Rafid M. AbdulAali; Usamah A. Alkarim A. Almunam Alshimaysawe; Ahmed Mohammed Ali (Kufa Journal for Agricultural Sciences)
The study aimed to isolate and diagnose fungi contaminating onion fruits and secreting mycotoxins, and to study the effect of Moringa oleifera extract on the growth of the fungus Aspergillus niger. The results of isolating fungi from onions showed the presence of the following fungi: Aspergillus niger, Fusarium sp., and Rhizopus stolonifer. It became clear that there was a predominance of the fungus A. niger, then the fungus Fusarium sp., followed by the fungus Rhizopus stolonifur, as their frequency rates reached 53.33, 36.66, and 10.00%, respectively, while the occurrence rate reached 83.33, 50.00, and 33.33%, respectively. In this study, molecular diagnosis of the fungus A. niger was carried out using internal transcribed spacer (ITS) genetic markers, and the results of chemical analysis using thin layer chromatography (TLC) showed that 9 of the 16 isolates were A. niger, isolated from onions, produced ochratoxin A with a production rate of 56.25%. The moringa extract inhibited the growth of the fungus A. niger, as the percentage of inhibition increased with increasing concentration, and the highest percentage of inhibition was at a concentration of 15%, which reached 47.32%. The percentage of inhibition was at concentrations of 5 and 10 (12.82 and 26.15%).